ALDEFLUOR activity, ALDH isoforms, and their clinical significance in cancers - Jiang-Jie Duan; Jiao Cai; Lei Gao; Shi-Cang Yu (Taylor & Francis Group, 2023)
High aldehyde dehydrogenase (ALDH) activity is a metabolic feature of adult stem cells and various cancer stem cells (CSCs). The ALDEFLUOR system is currently the most commonly used method for evaluating ALDH enzyme activity in viable cells. This system is applied extensively in the isolation of normal stem cells and CSCs from heterogeneous cell populations. For many years, ALDH1A1 has been considered the most important subtype among the 19 ALDH family members in determining ALDEFLUOR activity. However, in recent years, studies of many types of normal and tumour tissues have demonstrated that other ALDH subtypes can also significantly influence ALDEFLUOR activity. In this article, we briefly review the relationships between various members of the ALDH family and ALDEFLUOR activity. The clinical significance of these ALDH isoforms in different cancers and possible directions for future studies are also summarised.